Open distance education for teachers in Ukraine: the case of the Ukrainian Open University of Postgraduate Education - Mykola O. Kyrychenko; Olha V. Prosina; Yaroslava L. Shven; Tetiana S. Kravchynska (Academy of Cognitive and Natural Sciences, 2024)
The Ukrainian Open University of Postgraduate Education (UOUPE) is a self-governing educational institution that aims to provide distance education for teachers in the context of the COVID-19 pandemic and the integration of Ukraine into the European educational space. The UOUPE is based on a design-transforming nonlinear paradigm and a reflexive-positional approach, enabling a community of progressive educators who can respond to modern challenges and change their learning and professional practices. The paper presents the interregional cooperation project for teachers' professional development, which the UOUPE implements in collaboration with the Department of Philosophy and Adult Education of the Central Institute of Postgraduate Education of the University of Educational Management. The paper also reports the results of the first diagnostic stage of the project, which involved 120 teachers from different regions of Ukraine.